Directional Matrix Nanotopography with Varied Sizes for Engineering Wound Healing - Kim, Jangho; Bae, Won-Gyu; Kim, Yeon Ju; Seonwoo, Hoon; Choung, Han-Wool; Jang, Kyoung-Je; Park, Sunho; Kim, Bog Hee; Kim, Hong-Nam; Choi, Kyoung Soon; Kim, Myung-Sun; Choung, Pill-Hoon; et al. (WILEY, 2017)
Topographic features play a crucial role in the regulation of physiologically relevant cell and tissue functions. Here, an analysis of feature-size-dependent cell-nanoarchitecture interactions is reported using an array of scaffolds in the form of uniformly spaced ridge/groove structures for engineering wound healing. The ridge and groove widths of nanopatterns are varied from 300 to 800 nm and the nanotopography features are classified into three size ranges: dense (300-400 nm), intermediate (500-600 nm), and sparse (700-800 nm). On these matrices, fibroblasts demonstrate a biphasic trend of cell body and nucleus elongation showing the maximum at intermediate feature density, whereas maximum migration speed is observed at the dense case with monotonic decrease upon increasing feature size. The directional organization of cell-synthesized fibronectin fibers can be regulated differently via the nanotopographical features. In an in vitro wound healing model, the covering rate of cell-free regions is maximized on the dense nanotopography and decreased with increasing feature size, showing direct correlation with the trend of migration speed. It is demonstrated that the properties of repaired tissue matrices in the process of wound healing may be controlled via the feature-size-dependent cell-nanoarchitecture interactions, which can be an important consideration for designing tissue engineering scaffolds.
Keywords: SMOOTH-MUSCLE-CELL; EXTRACELLULAR-MATRIX; PROLIFERATION; TOPOGRAPHY; MIGRATION; COLLAGEN; FIBROBLASTS; SURFACES; GUIDANCE; DENSITY